2018
DOI: 10.1016/j.ssmph.2018.07.001
|View full text |Cite
|
Sign up to set email alerts
|

Perceived neighborhood disorder, racial-ethnic discrimination and leading risk factors for chronic disease among women: California Behavioral Risk Factor Surveillance System, 2013

Abstract: Social environmental factors are theoretically identified as influential drivers of health behaviors – tobacco smoking, alcohol consumption, and physical activity – related to chronic disease disparities. Empirical studies investigating relationships involving social environmental factors have found that either greater interpersonal racial-ethnic discrimination or perceived neighborhood disorder were associated with adverse health behaviors, with potentially larger effects among women. We simultaneously tested… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 56 publications
0
11
0
Order By: Relevance
“…[1][2][3] It is clear that the reasons for breast cancer mortality inequities are complex, 4,5 and might result from combined effects of intrinsic biological factors (e.g., hormone receptor status, genetic alterations, molecular subtypes) as well as non-biological factors (e.g., social determinants of health). In terms of the potential impacts of nonbiological factors that might contribute to aggressive breast cancer phenotypes and poorer outcomes, Black women tend to experience higher levels of health-adverse psychosocial stressors (e.g., discrimination, socioeconomic resources, social and physical disorder) than non-Hispanic White women in the United States (US), [6][7][8] which might lead to adverse health outcomes, [8][9][10][11] potentially including poorer breast cancer outcomes. Such experiences likely contribute to the cumulative physiologic stress and wear and tear on the body.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] It is clear that the reasons for breast cancer mortality inequities are complex, 4,5 and might result from combined effects of intrinsic biological factors (e.g., hormone receptor status, genetic alterations, molecular subtypes) as well as non-biological factors (e.g., social determinants of health). In terms of the potential impacts of nonbiological factors that might contribute to aggressive breast cancer phenotypes and poorer outcomes, Black women tend to experience higher levels of health-adverse psychosocial stressors (e.g., discrimination, socioeconomic resources, social and physical disorder) than non-Hispanic White women in the United States (US), [6][7][8] which might lead to adverse health outcomes, [8][9][10][11] potentially including poorer breast cancer outcomes. Such experiences likely contribute to the cumulative physiologic stress and wear and tear on the body.…”
Section: Introductionmentioning
confidence: 99%
“…Previous, mostly cross-sectional, studies have found that participant-perceived residential physical disorder indicators - lower aesthetic appeal, presence of garbage, graffiti, and poor building conditions - have been associated with participant-reported stress, alcohol consumption, tobacco use, physical activity, and various health outcomes ( Latkin and Curry, 2003 ; Mayne et al, 2018 ; Theall et al, 2013 ; Giurgescu et al, 2015 ; Plascak et al, 2018 ; O’Brien et al, 2019 ). Despite their importance investigating relationships between perceived environmental stressors and health outcomes, these studies are limited by the potential of same-source bias ( Chum et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…Perceptions of a range of neighborhood problems are associated with poorer self‐rated physical health (Godhwani et al, 2019), increased obesity rates (Burdette & Hill, 2008; Rooks et al, 2014), increased rates of alcohol use (Hill & Angel, 2005; Plascak et al, 2018), engagement in dating violence (Rothman et al, 2011) as well as dating violence victimization (Malik et al, 1997), and mortality among older adults (Wen et al, 2005). Negatively perceived neighborhoods were found to have higher noise levels and lower levels of safety, cleanliness, visual appeal, and reputation (Mouratidis, 2020).…”
Section: Introductionmentioning
confidence: 99%